2011
DOI: 10.1364/oe.20.000a13
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency white LEDs with single-crystal ZnO current spreading layers deposited by aqueous solution epitaxy

Abstract: Heteroepitaxial ZnO transparent current spreading layers with low sheet resistances were deposited on GaN-based light emitting diodes using aqueous solution phase epitaxy at temperatures below 90°C. The performance of the LEDs was analyzed and compared to identical devices using electron-beam evaporated indium tin oxide transparent current spreading layers. White LEDs with ZnO layers provided high luminous efficacy–157 lm/W at 0.5A/cm2, and 84.8 lm/W at 35A/cm2, 24% and 50% higher, respectively, than devices w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…18 The differential series resistance (R s ) of the reported LED was $0.02 X Â cm 2 . 18 We fit the experimental data to the diode equation…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…18 The differential series resistance (R s ) of the reported LED was $0.02 X Â cm 2 . 18 We fit the experimental data to the diode equation…”
mentioning
confidence: 95%
“…To estimate the efficiency of cascaded LED structures, we combine our estimates of tunneling resistance with the experimental data from the commercial LED published elsewhere so that nonidealities of the active region are taken into account. 18 The modeled reference LED emits at 470 nm and consists of a 1.02 mm 2 mesa area with ZnO layer as contact to p-GaN. 18 The differential series resistance (R s ) of the reported LED was $0.02 X Â cm 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ZnO film can also be used in gas sensor [7] and other fields. Reading et al [8] deposited ZnO film on GaN-based LEDs, finding that white LEDs with ZnO sheet has higher luminous efficacy than devices with indium tin oxide film. Kim et al [9] successfully grew heteroepitaxial ZnO films in water at 90 C using a two-step method, and they also demonstrated that the aqueous solution can synthesis ZnO nanowire array film in the same growth system by changing its potential of hydrogen (PH).…”
Section: Introductionmentioning
confidence: 99%
“…For the phosphor-free white LEDs, the laterally stacked structure of blue and green InGaN/GaN MQWs and monolithic polychromatic (LEDs) are demonstrated to grow white LEDs by multiple emission spectral and become the multicolor light-emitting sources [10], [11]. In addition, the ZnO current spreading is employed to compare the ITO due to lower sheet resistance and lower optical absorption [12].…”
Section: Introductionmentioning
confidence: 99%